Resistance of Ampicillin, Ceftazidime, and Cefotaxime in Poultry’s Escherichia coli (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2023)
Beta-lactam antibiotics are important antibiotics that are widely used in the field of human and animal health. Ampicillin resistance has been widely reported. Another increase in resistance is 3rd generation cephalosporins. The purpose of this study was to compare the ampicillin resistance profiles in 2019 and 2021 in the same E. coli isolates and to determine the resistance profiles of ampicillin, ceftazidime, and cefotaxime in live chicken E. coli. The research stages were the preparation of isolates; culture on differential selective media and checking the uniformity of bacterial cell morphology; biochemical test; bacterial DNA extraction; uspA gene amplification; visualization of amplification results; manufacture of bacterial suspensions; Kirby-Bauer disk diffusion resistance test; measurement of inhibition zones and determination of isolate status; and compared the ampicillin resistance test data. All isolates were confirmed positive for E. coli. The uspA gene (884 bp) was detected in all isolates. Ampicillin resistance in 2019 and 2021 in the same E. coli isolates when compared, there was no difference. Resistance test showed E. coli was resistant to ampicillin (100%), ceftazidime (15.4%), and cefotaxime (64.5%). The conclusion of the study was that there was no difference between the ampicillin resistance in 2019 and 2021 in E. coli isolates. Escherichia coli in this study had the highest resistance profile to ampicillin, followed by cefotaxime, and the lowest was ceftazidime.